Transforming India: Recent Trends in E-Governance (International Journal of Food and Nutritional Sciences, 2019)
The Digital India initiative, launched in 2015, has been a driving force behind the integrationof technology to streamline government services. Recent trends indicate a significant emphasison leveraging Aadhaar integration, mobile governance (m-Governance), and open governmentdata to enhance transparency, efficiency, and accessibility. The use of blockchain technologyin certain states reflects a commitment to secure and trustworthy digital transactions.